Characterization of citrus HSVd isolates - Palacio-Bielsa, Ana; Romero-Durbán, J.; Durán-Vila, Núria (2017)
Seven citrus isolates of Hop stunt viroid (HSVd) were subjected to retrotranscription and DNA amplification (RT-PCR), cloning and sequencing. Single stranded polymorphism (SSCP) analysis demonstrated the existence of variability among and within cachexia inducing sources of HSVd. The electrophoretic profiles of SSCP appeared to be able to discriminate between non-cachexia and cachexia sources of HSVd. Sequence analysis demonstrated that the variable (V) domain was very conserved among the cachexia variants. Five nucleotide differences, affecting both the upper (3 nucleotides) and the lower (2 nucleotides) strands of the V domain, were identified as a motif discriminating cachexia and non-cachexia sequences. These five nucleotides affect the organization of a short helical region and two flanking loops of the V domain probably modifying the three-dimensional geometry of the molecule. The stability of the minimum free energy rod-like conformation of the cachexia sequences is lower than the non-cachexia. Information regarding the host effect on the evolution and variability of viroid quasispecies is also provided.